Developing Electronic Student Worksheet of a Plane Solid Figure Based on Guided Inquiry for Junior High School Students - andriyani andriyani; Hesti Wulandari (International Journal on Emerging Mathematics Education, 2022)
In complete, this research aims to produce electronic student worksheets that are valid, practical, and effective in learning material of a plane solid figure at SMP Negeri 2 Bengkulu. This research is part of the comprehensive research that only focuses on producing valid and practical electronic student worksheets based on guided inquiry learning in plane shapes. Validity is based on the assessment of material experts and media experts on the feasibility of the material content and the media side. At the same time, practicality is measured by the utilization of electronic student worksheets during learning. This research includes development research using the ADDIE model, which contains five cyclic stages, namely (1) analysis, (2) design phase, (3) development, (4) implementation, and (5) evaluation. The analysis results show a need for students for guided inquiry-based electronic worksheets by adjusting the characteristics of students whose critical thinking skills are still low. In the design, the researcher designs the product according to the analysis results, which continues with the development stage to realize the product design at the previous stage becomes the prototype. At this stage, experts also carried out validity testing and product practicality testing at the implementation stage to obtain valid and practical electronic student worksheets based on guided inquiry learning, with evaluation stages carried out at each stage.